2003
DOI: 10.1021/jp0218950
|View full text |Cite
|
Sign up to set email alerts
|

Spin−Orbit Coupling Effect and Intramolecular Orbital Interactions:  Penning Ionization of CH2BrCl, CHBrCl2, and CH2BrCN by Collision with He*(23S) Metastable Atoms

Abstract: He*(2 3 S) Penning ionization electron spectra (PIES) as well as He I ultraviolet photoelectron spectra have been measured for CH 2 BrCl, CHBrCl 2 , and CH 2 BrCN. For the lower ionization-potential bands, spin-orbit split states are assigned in the spectra for CH 2 BrCl and CH 2 BrCN, whereas valence-orbital, ionic states are assigned for CHBrCl 2 . These assignments are based on the fact that the intramolecular orbital interactions in CHBrCl 2 are much stronger than those in the other molecules, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…These peaks we assign to a five photon ionization process with a total excitation energy of 11.5 eV and the formation of CH 2 BrCl + ͑X AЈ͒ ground state and electronically excited CH 2 BrCl + ͑Ã AЉ͒ parent ion. Tian et al 43 observed these similar two electron peaks separated by about 0.33 eV. This total excitation energy is also very close to the fragmentation threshold of 11.509 eV of CH 2 Cl + +Br͑ 2 P 3/2 ͒, so we do not think that direct five-photon excitation produces much fragmentation, as we should see a near 0 eV photoelectron peak.…”
Section: A Multiphoton Excitation and Photoelectron Spectrasupporting
confidence: 70%
See 2 more Smart Citations
“…These peaks we assign to a five photon ionization process with a total excitation energy of 11.5 eV and the formation of CH 2 BrCl + ͑X AЈ͒ ground state and electronically excited CH 2 BrCl + ͑Ã AЉ͒ parent ion. Tian et al 43 observed these similar two electron peaks separated by about 0.33 eV. This total excitation energy is also very close to the fragmentation threshold of 11.509 eV of CH 2 Cl + +Br͑ 2 P 3/2 ͒, so we do not think that direct five-photon excitation produces much fragmentation, as we should see a near 0 eV photoelectron peak.…”
Section: A Multiphoton Excitation and Photoelectron Spectrasupporting
confidence: 70%
“…7, we show the location of the lowest energy levels in the CH 2 BrCl + parent ion and the CH 2 Cl + +Br͑ 2 P 3/2 , 2 P 1/2 ͒ fragmentation channels. Photoelectron spectroscopy experiments 43 reveal that just above threshold there are four photoelectron bands related to the CH 2 BrCl + cation and they were observed at 10.75, 11.08, and 11.79 eV ͑unresolved structure͒. The first two bands at 10.75 and 11.08 eV correspond to ionization of the bromine lone-pair electron and the level is split as a result of the strong spinorbit coupling in CH 2 BrCl + due to the Br atom.…”
Section: A Multiphoton Excitation and Photoelectron Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The ordering of valence orbitals is adopted from the PES of Tian et al [3]. Figure 1 shows one of the ionization energy spectra of CH 2 BrCl over the energy range from 5 eV to 30 eV measured at azimuthal angles φ = 7°by EMS.…”
Section: Experimental Backgroundmentioning
confidence: 99%
“…synchrotron radiation light sources, Penning ionization electron spectra (PIES) [3] using He*(2 3 S) metastable atoms and photodissociation dynamics [5] using laser pulses. To our best knowledge, no electron momentum spectroscopy measurement on CH 2 BrCl has been reported so far.…”
mentioning
confidence: 99%